I suppose this is what you write are logarithms for base 2.
The following logarithmic rules can apply to each base:
n ∙ log ( a ) = log ( aⁿ )
log ( a ) + log ( b ) = log ( a ∙ b )
So:
3 log₂ ( 2 ) = log₂ ( 2³ ) = log₂ ( 8 )
log₂ ( 6 ) + 3 log₂ ( 2 ) = log₂ ( 6 ) + log₂ ( 8 ) = log₂ ( 6 ∙ 8 ) = log₂ ( 48 )
Log2(6)+3log2(2)
2 answers
or
since log₂ 2 = 1
we have:
log₂(6)+3log₂(2)
= (log₂ 6) + 3 , which is the same as log₂ 48 , Bosnian's answer
(not a better answer, just a different-looking answer)
since log₂ 2 = 1
we have:
log₂(6)+3log₂(2)
= (log₂ 6) + 3 , which is the same as log₂ 48 , Bosnian's answer
(not a better answer, just a different-looking answer)